Analisis Faktor Yang Mempengaruhi Financial Saticfaction Pada Dosen Di Universitas Papua - Agustia Said; Nurwidianto; Selmi Dedi (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2020)
The purpose of this study is to know whether financial knowledge, financial capability and financial behavior in partially and simultaneously that have affect to financial saticfaction. Then, to know which is most dominant factor that effect to financial saticfaction. The type of this research is quantitative that using numerical data to analyzed. The sample in this research is using proportionate stratified random sampling. Which is technique of collecting the data that using questionare distributed to lecturer at Universitas of Papua counted 83 samples. The data were analyzed using validity and reliability test, classic assumption test, multiple regression analysis (determination coefficient test, F tes and T Test) with SPSS 21 software support. The results of this study showed that the variables of financial knowledge and financial behavior influenced partially to financial saticfaction. While financial capability does not effect partially to financial saticfaction. Simultaneously, financial knowledge, financial capability and financial behavior have an effect to financial saticfaction. Then, the most dominant variable of financial behavior is affect to financial saticfaction.